The selection of appropriate Ro-Ro Vessel in the second-hand market using the WASPAS' Bonferroni approach in type 2 neutrosophic fuzzy environment. (January 2023) - Görçün, Ömer Faruk; Pamucar, Dragan; Krishankumar, Raghunathan; Küçükönder, Hande
Abstract: The second-hand vessel market has quite different dynamics than the market of the new-building vessel, and highly complicated and conflicting criteria and many uncertainties affect the ship selection process. Therefore, it is required to use a robust mathematical model to solve these kinds of decision-making problems. For this purpose, this paper presents an extended version of WASPAS (Weighted Aggregated Sum Product ASsessment) techniques with the help of T2NN based on the Bonferroni function (T2NN WASPAS'B). The three main focal points of the proposed approach are ( i ) setting the influential criteria to select the appropriate Ro-Ro vessel in the second-hand vessel market; and ( ii ) presenting a flexible group decision-making approach, which is proper to real decision-making problems. ( iii ) detecting the interrelations among criteria and eliminating the negative impacts of undesirable and excessive values in input variables on the results. Practical use of the proposed approach is demonstrated to select the appropriate Ro-Ro vessel in the second-hand market. The analysis results show that the most effective and determinative factor is Trailer Lane length, and the most effective alternative is GREIFSWALD. Besides, the consistency and validity of the obtained results have been verified with the help of a stability and robustness check. The results prove that the proposed novel T2NN WASPAS'B model is robust, powerful, and reliable for making rational and realistic decisions. Highlights: The current paper presents the T2NN WASPAS'B approach strengthen with the help of T2NN based on the Bonferroni function. The proposed model is applied to solve second-hand Ro-Ro vessel selection problems, which are highly complex and include uncertainties. It has identified the selection criteria for second-hand Ro-Ro ships for the first time. It presents a flexible decision-making approach, which is proper for real decision-making problems. It demonstrates interrelations among factors to make it more understandable in complex situations.